2021
DOI: 10.2217/nnm-2020-0467
|View full text |Cite
|
Sign up to set email alerts
|

DMSA-Coated Cubic Iron Oxide Nanoparticles as Potential Therapeutic Agents

Abstract: Aim: Superparamagnetic cubic iron oxide nanoparticles (IONPs) were synthesized and functionalized with meso-2,3-dimercaptosuccinic acid (DMSA) as a potential agent for cancer treatment. Methods: Monodisperse cubic IONPs with a high value of saturation magnetization were synthesized by thermal decomposition method and functionalized with DMSA via ligand exchange reaction, and their cytotoxic effects on HeLa cells were investigated. Results: DMSA functionalized cubic IONPs with an edge length of 24.5 ± 1.9 nm ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Higher ionization in an alkaline medium leads to ionized species and, as a result, increased repulsion from negatively charged species, resulting in colloidal stability. 35 , 36…”
Section: Results and Discussionmentioning
confidence: 99%
“…Higher ionization in an alkaline medium leads to ionized species and, as a result, increased repulsion from negatively charged species, resulting in colloidal stability. 35 , 36…”
Section: Results and Discussionmentioning
confidence: 99%
“…Zeta potentials (ζ) provide information about the charge distribution on the surface of the nanoconjugates. In general, absolute zeta potential values above 30 mV provide good stability and about 20 mV provide only short term stability, which is generally considered as a threshold value for the electrostatic stabilization, values in the range -5 mV to +5 mV indicate fast aggregation [31,32]. We performed zeta potential measurements at three various pH (pH=2, pH=7 and pH=12), where at 2 and 12 the hydrodynamic diameter of the NPs did not show any significant changes.…”
Section: Table 1 Hydrodynamic Sizes and Zeta Potentials Of C-fe3o4 Np...mentioning
confidence: 99%
“…26,84,129 In a recent study conducted ▣Citoglu et al, it was reported that 25 nm cubic SPIONs coated with DMSA possess a higher magnetisation compared to unmodified SPIONs (coated with decanoic acid). 130 The increase in M sat (DMSA coated = 89.6 emu g −1 and unmodified = 74.2 emu g −1 ) is hypothesised to be due the disulfide bonds from the DMSA molecule that can shorten the distance between MNPs and hence improve the magnetic properties (Fig. 7).…”
Section: Stabilisation Of Mnps Against Aggregationmentioning
confidence: 99%
“…7). 130 Furthermore, the free thiol and carboxylic groups of DMSA can be conjugated with antibodies, proteins or other drugs for biomedical applications. 129 However, Liu et al reported that DMSA coated MNPs could degrade into iron ions in an acidic environment inside the lysosome.…”
Section: Stabilisation Of Mnps Against Aggregationmentioning
confidence: 99%
See 1 more Smart Citation